Questioning EU citizenship: judges and the limits of free movement and solidarity in the EU - Thym, Daniel (Modern studies in European law, 2017)
Introduction : the judicial deconstruction of Union citizenship / Daniel Thym -- Extending citizenship rights and losing it all : brexit and the perils of "over-constitutionalisation" / Susanne K Schmidt -- The citizenship of personal circumstances in Europe / Dimitry Kochenov -- (De)Constructing the road to brexit : paving the way to further limitations on free movement and equal treatment? / Stephanie Reynolds -- Why did the citizenship jurisprudence change? / Urška Šadl and Suvi Sankari -- The evolution of citizens : rights in light of the European Union's constitutional development / Daniel Thym -- The engine of "europeanness" : free movement, social transnationalism and European identification / Ettore Recchi -- European citizenship and transnational rights : chronicles of a troubled narrative / Francesca Strumia -- Consolidating union citizenship : residence and solidarity rights for jobseekers and the economically inactive in the post-Dano era / Ferdinand Wollenschläger -- Back to the roots : no access to social assistance for Union citizens who are economically inactive / Paul Minderhoud and Sandra Mantu -- Integrating Union citizenship and the Charter of Fundamental Rights / Niamh Nic Shuibhne -- The constitutional status of foreigners and European Union citizens : loopholes and interactions in the scope of application of fundamental rights / Sara Iglesias Sánchez -- The integration exception : a new limit to social rights of third-country nationals in European Union law? / Karin De Vries -- Membership without naturalisation? : the limits of European Court of Human Rights case law on residence security and equal treatment / Clíodhna Murphy -- Conclusion : the non-simultaneous evolution of citizens' rights / Dora Kostakopoulou and Daniel Thym